Culture, Religion and the State: Towards a Multidisciplinary Approach to Ensuring Public Health During the COVID-19 Pandemic (and Beyond) - Gozum IE; Capulong HG; Gopez JM; Galang JR (Dove Medical Press, 2021)
Ivan Efreaim Gozum,1 Harvey Gain Capulong,1 Jose Ma Gopez,1 Joseph Renus Galang2,3 1Center for Christian Formation and Praxis, Angeles University Foundation, Angeles City, 2009, Philippines; 2Graduate School, Angeles University Foundation, Angeles City, 2009, Philippines; 3Theology and Religious Education Department, De La Salle University, Manila, 0922, PhilippinesCorrespondence: Ivan Efreaim Gozum Email gozum.ivanefreaim@auf.edu.phBackground: This research investigates different approaches by cultural, religious and political groups in ensuring public health during the COVID-19 pandemic. During the pandemic, several methods were done by governments and healthcare institutions to mitigate the spread of the virus.Methods: This study uses content analysis, specifically a literature review, on existing online literature found in online journals, books, and reports relevant to the COVID-19 pandemic. The paper presents the available qualitative data including substantive findings as well as theoretical and methodological foundations relevant to the topic.Results: Culture, religion and the state have roles to play in ensuring public health during the COVID-19 pandemic. These three areas can help in mitigating the transmission of the virus, managing patients, and aiding the rollout of COVID-19 vaccines.Conclusion: This paper ends by suggesting that, in ensuring public health during the COVID-19 pandemic, a multidisciplinary approach, involving a concerted effort among culture, religion and the state, is necessary. This approach is also recommended for any public health crisis in the future.Keywords: COVID-19, multidisciplinary approach, culture, religion, state